Combined Profiling of Transcriptome and DNA Methylome Reveal Genes Involved in Accumulation of Soluble Sugars and Organic Acid in Apple Fruits - Wenfang Ma; Baiyun Li; Litong Zheng; Yunjing Peng; Rui Tian; Yangyang Yuan; Lingcheng Zhu; Jing Su; Fengwang Ma; Mingjun Li; Baiquan Ma (Foods, 2021)
Organic acids and soluble sugars are the major determinants of fruit organoleptic quality. Additionally, DNA methylation has crucial regulatory effects on various processes. However, the epigenetic modifications in the regulation of organic acid and soluble sugar accumulation in apple fruits remain uncharacterized. In this study, DNA methylation and the transcriptome were compared between ‘Honeycrisp’ and ‘Qinguan’ mature fruits, which differ significantly regarding soluble sugar and organic acid contents. In both ‘Honeycrisp’ and ‘Qinguan’ mature fruits, the CG context had the highest level of DNA methylation, and then CHG and CHH contexts. The number and distribution of differentially methylated regions (DMRs) varied among genic regions and transposable elements. The DNA methylation levels in all three contexts in the DMRs were significantly higher in ‘Honeycrisp’ mature fruits than in ‘Qinguan’ mature fruits. A combined methylation and transcriptome analysis revealed a negative correlation between methylation levels and gene expression in DMRs in promoters and gene bodies in the CG and CHG contexts and in gene bodies in the CHH context. Two candidate genes (MdTSTa and MdMa11), which encode tonoplast-localized proteins, potentially associated with fruit soluble sugar contents and acidity were identified based on expression and DNA methylation levels. Overexpression of MdTSTa in tomato increased the fruit soluble sugar content. Moreover, transient expression of MdMa11 in tobacco leaves significantly decreased the pH value. Our results reflect the diversity in epigenetic modifications influencing gene expression and will facilitate further elucidating the complex mechanism underlying fruit soluble sugar and organic acid accumulation.